Roles of GluN2C in cerebral ischemia: GluN2C expressed in different cell types plays different role in ischemic damage. Issue 6 (10th December 2019) - Ding, Yue; Wang, Le; Huo, Yuexiang; Sun, Yanping; Wang, Long; Gao, Zibin; Sun, Yongjun
Abstract: Over the past decade, many studies have focused on clarifying the roles of different N‐methyl‐d ‐aspartate (NMDA) receptor subunits in cerebral ischemia, hoping to develop subunit‐selective drugs. Recently, more attention was given to studying the role of GluN2C in ischemia damage, which may lead to the development of new NMDA receptor antagonists for cerebral ischemia. Results showed that GluN2C inhibition or knockout can effectively alleviate the ischemic injury caused by middle cerebral artery occlusion and, contrarily, can aggravate the damage to hippocampal CA1 circuit caused by transient global cerebral ischemia. These results indicate the complicated roles of GluN2C in cerebral ischemia. In this minireview, we focus on these findings, describe the roles of GluN2C from different cell origins in ischemic damage, and explain the above inconsistent experimental results.